Chemical Stability of Cd(II) and Cu(II) Ionic Imprinted Amino-Silica Hybrid Material in Solution Media - Buhani, Narsito, Nuryono, Eko Sri Kunarti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2013)
Chemical stability of Cd(II) and Cu(II) ionic imprinted hybrid material of (i-Cd-HAS and i-Cu-HAS) derived from silica modification with active compound (3-aminopropyl)-trimethoxysilane (3-APTMS) has been studied in solution media. Stability test was performed with HNO3 0.1 M (pH 1.35) to investigate material stability at low pH condition, CH3COONa 0.1 M (pH 5.22) for adsorption process optimum pH condition, and in the water (pH 9.34) for base condition. Material characteristics were carried out with infrared spectrophotometer (IR) and atomic absorption spectrophotometer (AAS). At interaction time of 4 days in acid and neutral condition, i-Cd-HAS is more stable than i-Cu-HAS with % Si left in material 95.89 % (acid media), 43.82 % (close to neutral), and 9.39 % (base media).Keywords: chemical stability, amino-silica hybrid, ionic imprinting technique